Achieving superior lithium storage performances of CoMoO4 anode for lithium-ion batteries by Si-doping dual vacancies engineering. (15th February 2022) - Wang, Xuejia; Su, Ting; Luo, Yunan; Quan, Lijun; Zhong, Linping; Li, Ruizhi; Zhou, Ting; Liu, Mengjiao; Zhao, Yan; Lai, Xin; Bi, Jian; Gao, Daojiang
Abstract: Regarded as a promising anode material, CoMoO4 can reveal higher theoretical capacity (980 mAh g −1 ) in the context of completely reversible electrochemical reaction. Unfortunately, the large volume expansion, low conductivity and inferior cyclic stability are non-negligible, which have greatly limited its further development and application. Herein, a series of CoMo1- x Si x /2 O4-2 x ( x = 0, 0.1, 0.15, 0.2 and 0.25) anode materials have been successfully synthesized through a solid-state method. This heterovalent atom doped strategy can not only provide cationic vacancy (Mo vacancy) but also generate anionic vacancy (O vacancy). The results demonstrate that all the Si doped CoMoO4 samples exhibit superior electrochemical performances than that of the pure CoMoO4 although the produce of the dual vacancies has negligible influence on the microstructures of CoMoO4, which should be attributed to the synergistic effect of the Mo vacancy and O vacancy and thus leading to the lower optical band gap, the enhanced conductivity and the faster transport of lithium ions and electron. Particularly, when the content of Si-doping is set as 0.05, the obtained CoMo0.9 Si0.05 O3.8 sample displays the highest capacity (847.4 mAh g −1 ) up to 300 cycles at a current density of 200 mA g −1 . This work paves an effective strategy for constructing dual vacancies to promote the electrochemical performance of transition metal oxide anode materials. Graphical Abstract: Image, graphical abstract